A novel gold and SiO2 material based planar 5-element high HPBW end-fire antenna array for 300 GHz applications - Kamili Jagadeesh Babu; Aldhaheri Rabah W.; Nella Anveshkumar; Alharbi Khalid H.; Sheikh Muntasir M. (Open Physics)
This article is intended to propose a novel gold and SiO2 material based planar 5-element high half power beam-width (HPBW) end-fire antenna array for 300 GHz applications. The proposed radiating structure composes of a 5-element off-set feed rectangular patch antenna array fed by a tapered microstrip line to accomplish high HPBW. Off-set feeding and parasitic patch resonators are incorporated to access the end-fire radiation characteristics. This antenna operating frequency ranges from 277.5 to 315 GHz with a peak gain and HPBW of the antenna as 4.98 dBi and around 100°, respectively, at 300 GHz, making it a good radiator at the specified band. A gold material of thickness 5 μm is used as the metal, while the SiO2 with a thickness of 60 μm is adopted for the substrate material. Design, parametric analysis, and lumped element circuit models are also explored in this work. End-fire pattern, high HPBW, and good performance make this antenna to be eligible to use in THz applications such as imaging, scanning, communication, and bio-medical.